(3JjSjQ GdHjGf dCMcGe GdbQBfs - (3LeGd GdOjf eMeO Hf Ydj Hf YHO Gddg GdehRYj Gdjefj, GHf fhQ GdOjfs
(3ChdgG (B:s
(3bGd Gdabjg GdCLd GdChMO GdYdGeI LeGd GdOjf GdMeO ddg GdPi Ndb GdEfSGf , hYdeg GdbQBf , hageg GdHjGf , hQRbg Gdage hGdYQaGf s
(3BNQgG (B:s
(3BNQg eHJhQ , hBNQ GdehLhO efg CKfGA ShQI (B" (3GdJMQje (B" (3bhdg (B: (3hbGd eSQhb (B: (3hCfRd Gddg JYGdi (B:" (3jG CjgG GdfHi de JMQe eG CMd Gddg dc (B" s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfhGfGJ HGdMeQI s
(3Ydi MhGTjgG JYdjbGJ hJUMjMGJ s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJaSjQ hYdhe GdbQBfs